Kedudukan Terdakwa Sebagai Saksi (Saksi Mahkota) Terhadap Terdakwa Lain dalam Tinjauan Hukum Acara Pidana (Lex Jurnalica, 2015)
AbstractThe role of the accused as a witness to be part of the crime scene is considered to have potential in the unmasked crimes are more significant. This occurs when the crimes involve multiple actors performed together. He can provide important evidence about who was involved, what the role of each actor, how the crime was carried out, and where other evidence could be found. In order for the defendant as a witness is willing to cooperate in disclosure of a case, the public prosecutor to use the existing legal instruments in the Code of Criminal Procedure (Criminal Procedure Code). In Indonesia allows that